Antarctic total ozone anomaly during 1988 and 2002 springs - A. V. Grytsai (Ukrainian Antarctic Journal, 2005)
The total ozone content (TOC) variations in Antarctic region are considered using the TOMS satellite measurements. Main attention is devoted to ozone hole anomalous development in the 1988 and 2002 springs. The TOC planetary wave parameters in anomalous and typical years were compared. The TOC zonal mean increase relatively linear trend is equal 36 DU in 1988 and 60 DU in 2002. The evident TOC longitudinal contrast appeared in August of both anomalous years, one month before typical quasi-stationary wave development. The September zonal mean minimum was absent and TOC values exceeded typical at least from August to December. The first spectral components of zonal wave showed a considerable amplitude growing. Wave 1 amplitude in August and September was 2-3 times larger than in the neighboring years. In September 2002 the amplitude of wave 2 increased twice comparative to August in contrast to 1988. Characteristics of wave 3 did not change considerably relative to other years. Westward displacement of quasi-stationary wave minimum and maximum in 1988 and 2002 has been analyzed. At 65°S the minimum for September-November averaged distribution shifted by 50° and 70°, respectively. This feature could be considered as indication of tropospheric changes.